2019
DOI: 10.1515/cti-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Kitchen chemistry course for chemistry education students: influences on chemistry teaching and teacher education – a multiple case study

Abstract: This study introduces the Kitchen Chemistry (KC) course and its influences on chemistry education as a whole. KC is considered to be a life-relevant learning environment that engages learners in science through the pursuit of personally relevant and meaningful goals. KC, as a form of interdisciplinary learning, aims to develop boundary-crossing skills and to support the development of pupils’ scientific thinking. The purpose of this research was to determine how KC as a context-based teaching approach applies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 14 publications
3
21
0
1
Order By: Relevance
“…The active participation of students and the use of familiar materials can increase understanding, as well as opportunities for entrepreneurial potential (Nja & Neji, 2013). As with the results of this research, previous research has also shown that through cooking activities, students were motivated and enthusiastic, and provided positive feedback (Nuora & Välisaari, 2019). Students consider the implementation of STEM PBL in groups as a positive thing.…”
Section: Stem Pbl In the Fun Cooking Activity To Learn About The Collsupporting
confidence: 72%
See 1 more Smart Citation
“…The active participation of students and the use of familiar materials can increase understanding, as well as opportunities for entrepreneurial potential (Nja & Neji, 2013). As with the results of this research, previous research has also shown that through cooking activities, students were motivated and enthusiastic, and provided positive feedback (Nuora & Välisaari, 2019). Students consider the implementation of STEM PBL in groups as a positive thing.…”
Section: Stem Pbl In the Fun Cooking Activity To Learn About The Collsupporting
confidence: 72%
“…Other findings suggest that educators should help students synthesize multiple disciplines because interdisciplinary thinking does not emerge on its own. Cooking activities create a challenging integrative context for teaching chemistry, and offer new possibilities for teaching chemistry in a new learning environment, which goes beyond the chemistry laboratory (Nuora & Välisaari, 2019). One of the topics of chemistry that are closely related to cooking and food activities is the colloid system.…”
Section: Introductionmentioning
confidence: 99%
“…This is also in line with the regular usage of kitchen as a context for chemistry studying (e.g. Nuora & Välisaari 2019). When reflecting this against views of "use of context" in chemical education as described by Gilbert (2006), it is evident that themes of environmental chemistry are often not as tightly connected with the lives of students as e.g.…”
Section: Q4 "What Examples Of Extractions Can You Think Of?"supporting
confidence: 66%
“…Adhesives are readily available and packaged for safe and convenient use at home; however, many do not understand the complex organic chemistry behind these materials. Many students have used adhesives in everyday life, and research has shown that conducting chemistry experiments in a way that students can connect to real life improves their motivation and development of chemistry skills. , …”
Section: Introductionmentioning
confidence: 99%
“…We have chosen several readily available adhesives for students to study: epoxies, caulk, wood glue, white glue, and cyanoacrylates. These commonplace adhesives will aid students’ grasp on chemistry because of tangible and memorable results that students can connect with personal experience. , We present background information, and an experimental procedure for each material, along with pre- and postlab questions with sample answers for instructional aid. This educational tool kit provides the details necessary to teach organic and polymer chemistry concepts including the basics of arrow pushing mechanisms, polymer mechanics, and viscoelasticity to remote learning students.…”
Section: Introductionmentioning
confidence: 99%